Rejuvenation of a fishermen village: a case of koliwadas of Mumbai - Arora, Amarinder (SPA, Bhopal, 2017)
In the midst of the concrete jungle of Cuffe Parade in South of Greater Bombay lies a quaint fishing village- Machhimar Nagar. Juxtaposed on either side by squatter settlements (which take the name of Machhimar Nagar), and due to present infrastructural inadequacies, it is but taken as a slum. The local community of people residing in this village i.e. the Koli people were the first inhabitants of Mumbai and have since been living along the entire coastline of Mumbai. Albeit the community holds the right to the land they live on, every passing development plan neglects their needs and interests. To add to the misery, due to the vast expanse of the Arabian Sea and a grand view, numerous reclamation schemes have been proposed to completely wipe the Kolis and their village off the map of Mumbai. Presently, the government has come out with the scheme of redeveloping these fishing villages, but no action has been towards implementation. The proposed study/ site area is a congested village with closely packed rows of single-storey houses, dingy narrow streets, cramped spaces for work/ leisure activities, and absolutely abysmal state of sanitation and hygiene.Moreover, it is completely secluded from the surrounding posh neighbourhood of Cuffe Parade due to lack of empathy from the residents, the constant feeling of exclusion, and the unparalleled deviation in the economic status of the two. Due to this reason and the ones stated above, the present generation of fisherfolk is not deeply rooted in the long-withstanding culture of the community and their livelihood of fishing, getting further alienated from themselves and the city. With the presence of water as the visual dimension for the residents and the livelihood of Koli people, this thesis aims at bridging the gap between the neighbouring residents and integrates the fishing community in the fabric of South Bombay, thus creating a sense of belongingness to the city which is their own. More importantly, the thesis aims at giving a viable proposal to improve the quality of life of Kolis through planning and design of the village. The proposed path for the same is thought to be sought by using phasing as a tool. The major scope of the thesis is to explore the potential of the framework and approach taken in bringing inclusiveness to and for the fisher community, and how beneficial it can be on a broader spectrum while sighting other existing Koliwadas, which are spread across Maharashtra, Andhra Pradesh and Gujarat .
Keywords: B. Arch